Risks In Provision Of Collateral Free Individual Loans: A Case Study Of Bank Rakyat Indonesia - Parid, Parid; Widiyono, Try (International Journal of Educational Research & Social Sciences, 2023)
Collateral Free Loans is a bank loan product offered by banks as lenders with the advantage that customers as prospective borrowers are not asked to provide collateral or guarantees in the form of any assets as a condition for being able to borrow money. The advantage of this loan is that someone can apply for credit without guaranteeing their goods. However, the absence of collateral in granting credit sometimes creates problems for the parties, especially the bank as the lender. This study aims to answer the question of how the risk is in providing individual loan without collateral carried out by Bank BRI, and how the application of the prudential principle in managing the risk of individual loans without collateral at Bank Rakyat Indonesia (BRI). This is a qualitative research with a case study approach. Data collection is done by interviews, observation and documentation. The results of this study indicate that the risks faced by banks in efforts to provide individual loan without collateral are 3 factors. The first is non-compliance with the standard requirements for granting credit which includes data collection, data analysis and preparation of conclusions and recommendations. Second, the authenticity of important documents that must also be attached is sometimes doubted. Third, the occurrence of irregularities in paying debts by the payer/treasurer. To minimize the risk of lending, BRI applies the prudential principles in accordance with banking laws through credit analysis which consists of 5 (five) principles, namely character, capital, capacity, condition, and collateral, with an emphasis on 2 aspects, namely character and capacity. These two principles are in line with the fiduciary principle and prudential principle in banking law.